Issue of Microfinance in Rural Areas: - (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Technology, innovation, and knowledge have become the key drivers of economic growth today. A broad scan, across many industry verticals, suggests that much of the economic growth of the last decade has been facilitated by the existence of strong technology platforms. The effective absorption and utilization of data and information is extremely important for any sector at various developmental stages. However, the importance of data management becomes more pronounced at the advent of the growth stage when an industry is expanding and diversifying rapidly. This is the state in which the Indian Microfinance industry is in today. As a result, microfinance practitioners‟ motivations to use technology interventions are the same as those for any other similar business model: technology’s ability to speed up the flow of information and capital, automate transactions, control and analyze data, improve customer experience, reduce transaction costs, and increase efficiency and customer outreach. Technology’s potential has, therefore, led Microfinance stakeholders to believe that technology can have a profound impact on their operations. As a result, technology’s promise and potential is being explored by both technology providers and microfinance institutions.